Evaluation of Selected Frost-Susceptibility Test Methods. - Chamberlain,Edwin J. (1986)
Three methods for determining the frost susceptibility of soils are evaluated in this report. These methods are the U.S. Army Corps of Engineers frost design soil classification system, a moisture-tension/hydraulic-conductivity test, and a laboratory freeze-thaw test. The Corps method, which is based on particle size, soil classification, and a laboratory freezing test, was found to be useful for identifying frost-susceptibility. The moisture-hydraulic-conductivity test was found to be unacceptable because it required too much time and its results correlated poorly with field observations. The freeze-thaw test was determined to be the most accurate of the methods studied, including the freeze test that is a part of the Corps method. The freeze-thaw test is thoroughly described. It includes indexes of both frost-heave susceptibility (heave rate) and thaw-weakening susceptibility (CBR after thawing). It also accounts for the effects of freeze-thaw cycling and is completely automated to improve the repeatability of the test results. It is suggested that the freeze-thaw test considered as a replacement for the Corps freezing test.